Pengaruh Fee Audit, Audit Tenure, Rotasi Audit dan Reputasi Auditor Terhadap Kualitas Audit pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Indonesia Tahun 2020-2022: The Effect of Audit Fees, Audit Tenure, Audit Rotation and Auditor Reputation on Audit Quality in Miscellaneous Industry Sector Manufacturing Companies Listed in Indonesia in 2020-2022 - Hidayati, Rafika Iftitah; Djamil, Nasrullah (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2024)
This research is a quantitative study that aims to determine how the effect of audit fees, audit tenure, audit rotation and auditor reputation on audit quality in various industrial sector manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The number of samples in this study were 20 companies with a sample withdrawal method using purposive sampling method, this study used secondary data obtained from the Indonesia Stock Exchange. The data analysis tool uses spss ver 27. While the data processing method used is logistic regression analysis. The results of partial hypothesis research show that the audit fee variable, Audit Tenure and audit rotation have a significant effect on audit quality. Meanwhile, the auditor reputation variable has no significant effect on audit quality. The result of the coefficient of determination (Nagelkerke R Square) is 0.752, this indicates that the contribution of all independent variables in explaining the dependent variable is 75%.